Premature ejaculation: prevalence in Asia Pacific - Lee, G. (Blackwell Publishing, 2010)
INTRODUCTION: Premature ejaculation (PE) is a common male sexual dysfunction. The prevalence of PE in the Asia-Pacific region has not been comprehensively studied. AIM: The aim of this study is to evaluate PE prevalence in nine Asia-Pacific countries and the impact of PE on sufferers. METHODS: A random sample of heterosexual males aged 18-65 years in a stable sexual relationship currently or in the past 2 years completed a 48-question survey by computer-assisted interviewing, online, or in-person; the survey and recruitment methodologies varied by location. The survey included demographic questions, the five-question Premature Ejaculation Diagnostic Tool (PEDT), the five-question Sexual Health Inventory for Men (SHIM), and the 10-question Index of Premature Ejaculation (IPE). Separately, men self-reported having PE (lifelong or acquired) or erectile dysfunction (ED). MAIN OUTCOME MEASURES: The PEDT was used to diagnose PE or probable PE; the SHIM was used to diagnose ED; and the IPE was used to assess respondent's attitudes toward PE. RESULTS: Of the 4,997 men who completed the survey, the prevalences of PEDT-diagnosed PE, PEDT-diagnosed probable PE, and self-reported PE were 16%, 15%, and 13%, respectively. Less than half of men with PEDT-diagnosed PE (N = 816) or probable PE (N = 738) self-reported the condition (40% and 19%, respectively), and 6% of men with a PEDT diagnosis of no PE self-reported PE. In contrast, more respondents self-reported ED (8%) than had SHIM-diagnosed moderate or severe ED (5%). IPE responses indicated that 45%, 46%, and 23% of men with PEDT-diagnosed PE were somewhat or very dissatisfied with the length of intercourse before ejaculation, their control over ejaculation, and with sexual intercourse, respectively. CONCLUSIONS: In this study, PE was more prevalent than ED in the Asia-Pacific countries surveyed, but only 40% of men with PEDT-diagnosed PE self-reported PE.